Factors Associated With Long-term Outcomes After Injury: Results of the Functional Outcomes and Recovery After Trauma Emergencies (FORTE) Multicenter Cohort Study. Issue 6 (June 2020) - Haider, Adil H.; Herrera-Escobar, Juan P.; Al Rafai, Syeda S.; Harlow, Alyssa F.; Apoj, Michel; Nehra, Deepika; Kasotakis, George; Brasel, Karen; Kaafarani, Haytham M. A.; Velmahos, George; Salim, Ali
Abstract : Objective: The aim of this study was to determine factors associated with patient-reported outcomes, 6 to 12 months after moderate to severe injury. Summary of Background Data: Due to limitations of trauma registries, we have an incomplete understanding of factors that impact long-term patient-reported outcomes after injury. As 96% of patients survive their injuries, several entities including the National Academies of Science, Engineering and Medicine have called for a mechanism to routinely follow trauma patients and determine factors associated with survival, patient-reported outcomes, and reintegration into society after trauma. Methods: Over 30 months, major trauma patients [Injury Severity Score (ISS) ≥9] admitted to 3 Level-I trauma centers in Boston were assessed via telephone between 6 and 12 months after injury. Outcome measures evaluated long-term functional, physical, and mental-health outcomes. Multiple regression models were utilized to identify patient and injury factors associated with outcomes. Results: We successfully followed 1736 patients (65% of patients contacted). More than half (62%) reported current physical limitations, 37% needed help for at least 1 activity of daily living, 20% screened positive for posttraumatic stress disorder (PTSD), all SF-12 physical health subdomain scores were significantly below US norms, and 41% of patients who were working previously were unable to return to work. Age, sex, and education were associated with long-term outcomes, while almost none of the traditional measures of injury severity were. Conclusion: The long-term sequelae of trauma are more significant than previously expected. Collection of postdischarge outcomes identified patient factors, such as female sex and low education, associated with worse recovery. This suggests that social support systems are potentially at the core of recovery rather than traditional measures of injury severity.